2020
DOI: 10.1021/acs.chemmater.0c01255
|View full text |Cite
|
Sign up to set email alerts
|

Halide Mixing and Phase Segregation in Cs2AgBiX6 (X = Cl, Br, and I) Double Perovskites from Cesium-133 Solid-State NMR and Optical Spectroscopy

Abstract: All-inorganic double perovskites (elpasolites) are a promising potential alternatives to lead halide perovskites in optoelectronic applications. Although halide mixing is a well-established strategy for band gap tuning, little is known about halide mixing and phase segregation phenomena in double perovskites. Here, we synthesize a wide range of single- and mixed-halide Cs 2 AgBiX 6 (X = Cl, Br, and I) double perovskites using mechanosynthesis and probe their atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 87 publications
4
54
0
Order By: Relevance
“…It has previously been found that the (practical) detection limit for iodide substituting bromide in a ternary metal compound by disorder-induced broadening of 133 Cs NMR signals is around 2%. 58 A similar limit may pertain here for substitutional Sn detection, although two factors suggest that 133 Cs NMR could be less sensitive to doping in our case. Firstly, since the average Sn ionic radius is much more similar to that of Bi( iii ) than the iodide radius is to the bromide radius, it is reasonable that Sn substitution would lead to less structural distortion.…”
Section: Resultssupporting
confidence: 65%
“…It has previously been found that the (practical) detection limit for iodide substituting bromide in a ternary metal compound by disorder-induced broadening of 133 Cs NMR signals is around 2%. 58 A similar limit may pertain here for substitutional Sn detection, although two factors suggest that 133 Cs NMR could be less sensitive to doping in our case. Firstly, since the average Sn ionic radius is much more similar to that of Bi( iii ) than the iodide radius is to the bromide radius, it is reasonable that Sn substitution would lead to less structural distortion.…”
Section: Resultssupporting
confidence: 65%
“… 54,55 A similar nonlinear change in 133 Cs NMR chemical shifts was recently reported for mixed-halide double perovskites Cs 2 AgBi(Cl 1− x Br x ) 6 due to a non-additive effect of nearest and next-nearest neighbours on the chemical shift for 133 Cs nuclei and the associated extended halide environment. 56 …”
Section: Resultsmentioning
confidence: 99%
“…[103] Interestingly, the mixing of chloride and bromide does not change the PL emission peak significantly, possibly because of the large electron-phonon coupling and broad STE emission which is not substantially dependent on halide composition. [104,105] Unfortunately iodide can only be incorporated into bromide or chloride lattice at low concentration (<3 mol%) because higher alloying level results in non-perovskite phases. [104] Additionally, mixing sulphide and bromide (Cs 2 AgBiBr 5.8 S 0.1 ) is demonstrated to slightly contract the bandgap by shifting up the valence band edge.…”
Section: Bandgap Engineeringmentioning
confidence: 99%
“…[104,105] Unfortunately iodide can only be incorporated into bromide or chloride lattice at low concentration (<3 mol%) because higher alloying level results in non-perovskite phases. [104] Additionally, mixing sulphide and bromide (Cs 2 AgBiBr 5.8 S 0.1 ) is demonstrated to slightly contract the bandgap by shifting up the valence band edge. [106] Recently, we have reported an effective way to enhance the light harvesting of Cs 2 AgBiBr 6 by using Cu doping.…”
Section: Bandgap Engineeringmentioning
confidence: 99%